The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.5812/ijem-127445
|View full text |Cite
|
Sign up to set email alerts
|

Inflammatory Markers and Atherogenic Coefficient: Early Markers of Metabolic Syndrome

Abstract: Background: Considering the close link between metabolic syndrome (MetSyn) and cardiovascular diseases, considerable attention has been devoted to the identification of their shared underlying pathological mechanisms in recent decades. Objectives: This study aimed to investigate the association between pro-inflammatory factors and newly-diagnosed MetSyn. Methods: This case-control study recruited obese and nonobese individuals who were newly diagnosed with MetSyn (cases, n = 84) and healthy individuals (contro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…Different studies have concluded that low values in VLF are related to worse clinical outcomes in different pathological conditions, providing even greater prognostic value than LF or HF [13,[42][43][44]. Likewise, an inverse relationship between VLF and proinflammatory states has been reported in several studies [45][46][47], which could be related with MS, since it is considered a condition which coexists with a low-grade chronic inflammatory processes [47].…”
Section: Discussionmentioning
confidence: 98%
“…Different studies have concluded that low values in VLF are related to worse clinical outcomes in different pathological conditions, providing even greater prognostic value than LF or HF [13,[42][43][44]. Likewise, an inverse relationship between VLF and proinflammatory states has been reported in several studies [45][46][47], which could be related with MS, since it is considered a condition which coexists with a low-grade chronic inflammatory processes [47].…”
Section: Discussionmentioning
confidence: 98%
“…Meanwhile, modi ed LDLs had the ability to activate the toll-like receptors, thereby priming the Nod-like receptor protein 3 in ammasomes and ultimately lead to the activation of interleukin-1β and secondary in ammatory responses [19]. In newly diagnosed patients with metabolic syndrome, there were associations between TNF-α and fasting blood glucose (r = 0.179, P = 0.021), LDL-C (r = 0.199, P = 0.01), atherogenic index (r = 0.219, P = 0.004), TG (r = 0.351, P < 0.001), and HDL-C (r = -0.244, P = 0.001) [20]. Among individuals without severe cardiovascular risks, there was a positive association between serum TG and high-sensitivity C-reactive protein (CRP) (r = 0.298, P < 0.001) [21].…”
Section: Discussionmentioning
confidence: 99%
“…More recent reports indicate that tau protein/β-amyloid ratio increases in the cerebro spinal fluid after a surgical procedure, independent of the class of anesthetic used, additionally raising doubt about the foretelling quality of the biomarkers [1,14]. Chronic inflammatory disorders such as diabetes mellitus, metabolic syndrome or atherosclerosis have been pinpointed as favouring factors for postoperative cognitive decline, as well as anesthetic drugs, duration of the surgical procedure and pain [15,16]. No significant difference was found between emergency or elective surgery settings in regards to the incidence of early postoperative cognitive decline [17].…”
Section: Introductionmentioning
confidence: 99%